comparison of differnt extraction methods for the extraction of bioactive components of Senna alexandrina - Noora Enayati; Reza Ghafarzadegan; Reza Hajiaghaee; Mehdi Vazirian (Institue of Medicinal Plants, ACECR, 2017)
Background and Purpose: Senna leaf is among the category stimulant laxatives. The laxative effect of this medicinal plant refers to sinusoids, aloe emodin and dynatron within it that all of them are among anthraquinone derivatives used for the treatment of constipation, discharge of the intestine before surgery or abdomen surgeries and tests. One of the most important issues raised in the extraction of active ingredients in the natural medicinal sources, is in the analysis and industry sectors, type and method of extraction of these substances to increase efficiency and extraction of these substances. This study was conducted to compare different extraction methods of the plant of Senna and to optimize the extraction of the active substance of B sinusoid using the statistical methods of response surface. Methods: For the extraction of Senna extract, various extraction methods, including maceración, dynamic maceración (stirrer), ultrasound waves, microwaves and Soxhlet with 96 and 60% ethanol solvents were used at different times. The best method with considering the weight means of the extract and active substance of B sinusoid was selected. In the next phase, using the statistical method of response surface, the amount of active substance of B sinusoid was optimized. Results: The results of ANOVA showed that with considering the weight mean of the extract and amount of B sinusoid, stirrer method is the most suitable method for the extraction of Senna in the industrial and medicinal extraction. The optimization results for the best extraction method using the response surface, according to the influential variables showed that when accessing the maximum amount of the active substance (3.009%) occurs that temperature, time, the ratio of substance to solvent and filter are 84°C, 119.7 minutes, 0.04 and 29.7 micron, respectively. Conclusion: Finally, it can be concluded that using active maceración extraction method (stirrer) is suggested as one of the best method for the extraction of Senna extract in industry and the output efficiency of the active substance of B sinusoid under the impact of the introduced optimized conditions will be at the maximum level.